PENGEMBANGAN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) BERBASIS KOOPERATIF TIPE TGT MATERI GETARAN DAN GELOMBANG - Renita Aprilia; Nur Kuswanti; Oktaffi Arinamanasikana (Discovery, 2021)
This research is initialized by the teacher-centered science learning process, thelimited use of learning tools in the form of lesson plans, the less varied use of learningmodels and games making students understand easily. The objectives are describing: theprocess of developing TGT cooperative-based RPP on vibration and wave material and thefeasibility of TGT-based cooperative learning plans on material vibrations and waves. Thedevelopment model used was ADDIE model consisting of 5 stages, namely Analysis,Design, Development, Implementation and Evaluation but the Implementation stage wasnot implemented. The validity data used RPP validation sheet. This development researchresulted in a TGT-based cooperative learning plan (RPP) product. The results indicatedthat the process of developing a lesson plan refers to the ADDIE development model.Analysis consisted of 3 steps covering needs analysis, curriculum analysis and materialanalysis. Design was carried out by collecting references and compiling a cooperative RPPbased on the TGT type. Development was assessed by experts consisting of 3 validators,namely 2 lecturers of natural science education courses and 1 junior high school teacher.From the results of the assessment obtained validity assessments as well as input andsuggestions from the validator used to produce the final RPP product. The Evaluation stepwas carried out at each stage. The quality of the TGT cooperative learning based learningplan on vibration and wave material developed based on validity was declared feasible touse because the validation results obtained a score of 4.78 with a very valid category.Keywords: Development of lesson plan, Cooperative Learning, TGT (Teams GamesTournament), ADDIE development model.